The diffusion of incel culture into digital spaces and its negative sociocultural implications - Pfister, Nicole, author (Colorado State University. Libraries, 2026)
A new phenomenon has emerged online where many young men have begun to identify as being involuntarily celibate (Sparks et al., 2024). Also known as incels, these individuals report being unsuccessful in obtaining heteronormative sexual and romantic relationships. These men believe that women hold the power to control relationships that purposefully exclude unattractive men with the aid of a societal hierarchy that hyperfocuses on appearance, wealth, and status. With the increasing popularity of algorithmic social media platforms such as Instagram and TikTok, the manosphere is beginning to infiltrate mainstream digital spaces. This project seeks to analyze existing literature that looks at specific platforms where this content is found, what this content looks like, and what makes this content so engaging. This project will also look at the archetype of incels as well as the potential political implications of this framework. Consequently, women may begin to see less representation, advocacy of rights, and protections against harm in a variety of different spaces. It is important to dissect the societal implications of this digital crisis for both men and women. Incel ideology may erode the opportunity for individuals to engage in healthy interpersonal relationships based on equity over dominance.
Keywords: incels; algorithms; misogyny; relationships; violence